A novel single-phase ZCS-PWM high power factor boost rectifier - Canesin, Carlos A. [UNESP]; Barbi, Ivo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1997)
This paper presents a novel single-phase high power factor PWM boost rectifier, featuring soft commutation of the active switches at zero-current (ZCS). It incorporates the most desirable properties of the conventional PWM and the soft-switching resonant techniques. The input current shaping is achieved with average current mode control, and continuous inductor current mode. This new PWM converter provides ZCS turn-on and turn-off of the active switches, and it is suitable for high power applications employing IGBTs. Principle of operation, theoretical analysis, a design example, and experimental results from a laboratory prototype rated at 1600 W with 400 Vdc output voltage are presented. The measured efficiency and power factor were 96.2% and 0.99 respectively, with an input current THD equal to 3.94%, for an input voltage THD equal to 3.8%, at rated load.
Keywords: Total harmonic distortion (THD); Zero current switching (ZCS); Bipolar transistors; Electric commutation; Electric current control; Electric distortion; Electric inductors; Electric network analysis; Electric network topology; Electric power factor; Electric switches; Pulse width modulation; Resonant circuits; Switching circuits; Electric rectifiers